2014
DOI: 10.1016/j.imlet.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Double negative (CD19+IgG+IgD−CD27−) B lymphocytes: A new insight from telomerase in healthy elderly, in centenarian offspring and in Alzheimer's disease patients

Abstract: a b s t r a c tImmunosenescence is characterized by the impairment of humoral immunity with changes in the memory/naive B cell compartment. In particular we have previously reported the percentage increase of a Memory IgD − CD27 − (Double Negative, DN) B cell population in aged people. In this study, we have further characterized DN B cells with the aim to better understand their contribution to immunosenescence. As DN B cells show a poor ability to proliferate in vitro, we have evaluated the expression of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 60 publications
1
24
0
Order By: Relevance
“…Immunosenescence is characterized by the impairment of humoral immunity with changes in the memory/naive B cell compartment (Martorana et al 2014). The increase of memory B cells (IgG(+) IgD(-)CD27(-), double negative, DN) population in the elderly, in which there is also a typical inflammatory micro-environment.…”
Section: B Lymphocytesmentioning
confidence: 99%
See 1 more Smart Citation
“…Immunosenescence is characterized by the impairment of humoral immunity with changes in the memory/naive B cell compartment (Martorana et al 2014). The increase of memory B cells (IgG(+) IgD(-)CD27(-), double negative, DN) population in the elderly, in which there is also a typical inflammatory micro-environment.…”
Section: B Lymphocytesmentioning
confidence: 99%
“…In the elderly, naïve/memory B cell populations present a different expression of the studied receptors that could be discussed in terms of "inflamm-aging". In particular IgG(+)IgD(-)CD27(-) DN B cells show a tissue trafficking phenotype and they can be stimulated to produce granzyme B (Bulati et al 2014). Double negative (IgG+IgD-CD27-) B cells are increased in a cohort of moderate-severe Alzheimer's disease patients and show a pro-inflammatory trafficking receptor phenotype (Bulati et al 2015).…”
Section: B Lymphocytesmentioning
confidence: 99%
“…A double-negative B lymphocyte is a recently recognized B cell entity of which exact role and origin remain to be demonstrated. However, increasing evidences suggest that they belong to memory B cell category, but are incapable of antigen presentation or replication, so-called "exhausted" or "senescent" memory B cells [12,13]. Expansion of DN B lymphocytes has been reported in elderly population or various chronic inflammatory conditions; Alzheimer' s disease (AD) [14], rheumatoid arthritis (RA) [15], systemic lupus arthritis (SLE) [16], and chronic Human Immunodeficiency Virus (HIV) [17].…”
Section: Discussionmentioning
confidence: 99%
“…115 Moreover, Martorana et al found an augmented subset of B cells with a memory doublenegative phenotype in elderly people. 116 Interestingly, Colonna-Romano et al reported that B cells are late memory or exhausted cells, which may be a manifestation of ageing or a dysregulation of the immune system. 117 …”
Section: Recent Advances In Alzheimer's Diseasementioning
confidence: 99%